Fertilizer placement affects weed growth and grain yield in dry-seeded rice (Oryza sativa L.) systems. - Chauhan, Bhagirath S.; Abugho, Seth B. (Scientific Research Publishing, Inc., 2013)
A study was conducted in a split-plot design to evaluate the effect of fertilizer placement method on weed growth and grain yield in a dry-seeded rice (DSR) system. Main-plot treatments were four fertilizer placement methods: between narrow rows (between 15-cm-wide rows of the pattern 25-15-25 cm), between uniform rows (between 20-cm-wide rows), within uniform rows, and surface broadcast. Subplot treatments were three weed control methods: herbicide-treated, nontreated, and weed-free. Weed biomass was greater in the nontreated plots than in the herbicide-treated plots. Herbicide application reduced weed biomass by 89% to 99% compared with the nontreated control. Fertilizer placement did not influence weed biomass in the herbicide-treated plots; however, it greatly influenced biomass in the nontreated plots. Fertilizer placement on the surface increased weed biomass (69 -71 g·m–2) compared with the placement of fertilizer below the soil surface (37 -57 g·m–2). Fertilizer placement did not influence weed density and biomass at 60 days after planting. Nontreated plots yielded 700 to 2080 kg·ha–1. Grain yield was similar between the herbicide-treated (2660-3250 kg·ha–1) and weed-free (2620-3430 kg·ha–1) plots. Grain yield was not influenced when basal fertilizer was banded within (2390-2500 kg·ha–1) or between rows (2530-2650 kg·ha–1). However, grain yield decreased when basal fertilizer was broadcast on the soil surface (2200 kg·ha–1). The results of our study demonstrated that rice yield was usually lower with surface broadcast of fertilizer than with subsurface fertilizer treatments. In conclusion, surface broadcast of basal fertilizer may result in high weed pressure in DSR systems.